2013
DOI: 10.5430/jnep.v3n9p187
|View full text |Cite
|
Sign up to set email alerts
|

Six thinking hats as a creative approach in managing meetings in hospitals

Abstract: Background: Meeting is a purposeful gathering of people, a goal oriented work session, a productive use of communal time and a cooperative group effort. Six thinking hats approach aims to encourage parallel thinking, full-spectrum thinking and to separate ego from performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The effectiveness of using six thinking hats to guide the meeting process to achieve a meeting's purpose with productive use of communal time and cooperative group effort has been reported by Taie and El kamel (). Findings by Mitez () supported this showing use of six thinking hats in meetings engaged and empowered all stakeholders and saved time by organizing thinking.…”
Section: Collaborative Care Meetingsmentioning
confidence: 96%
“…The effectiveness of using six thinking hats to guide the meeting process to achieve a meeting's purpose with productive use of communal time and cooperative group effort has been reported by Taie and El kamel (). Findings by Mitez () supported this showing use of six thinking hats in meetings engaged and empowered all stakeholders and saved time by organizing thinking.…”
Section: Collaborative Care Meetingsmentioning
confidence: 96%
“…It is not only an easy-to-use method but also adaptable for different targets and target audiences. Hence, other papers have recommended this method for a variety of purposes, such as collaborative care [45], relationship counseling [46], work meetings [47], and education [48].…”
Section: Lessons Learnedmentioning
confidence: 99%
“…Research has shown that creativity can be enhanced through explicit training [33]. Azeez [34] conducted a study demonstrating that the six thinking hats technique significantly improved participants' innovative competence. The results indicated that the experimental group outperformed the control group on the innovative competence scale, suggesting that the training had a positive impact.…”
Section: Introductionmentioning
confidence: 99%